TEACHER’S KNOWLEDGE, SKILLS AND ATTITUDES TOWARDS THE IMPLEMENTATION OF PRESCHOOL CURRICULUM INNOVATIONS - Romarzila Omar, Hazhari Ismail, Ruslan Abdullah, Zanaton Hj Iksan, Rosniza Mohamed Zain (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This article reports the results of a study on the Teacher’s Knowledge, Skills and Attitudes towards the Implementation of Preschool Curriculum Innovations. The implementation of curricular innovations is a complex process. Studies on curricular changes have shown that teachers play a pivotal role in the success or the failure of implementation projects. The study focuses on teachers’ perceptions and attitudes toward the implementation of the newly introduced National Preschool Curriculum Standards (NPCS) in Malayisan preschools. The study uses the survey method involving preschool teachers set to explore the teachers’ level of knowledge about the curricular innovations, the teachers’ level of skill in implementing the curricular innovations, and the teachers attitudes towards the change. Data was gathered using questionnaires that captured teachers knowledge, skills and attitudes towards NPCS. Findings showed that teachers had high mean score on knowledge of NPCS and positive attitudes towards the curricular innovations. However the low to moderate mean score on teachers’ skills in implementing curricular changes indicate that they are not ready and lack in proficiencies to implement the changes as required. The results suggest that teachers need professional development promoted by personal learning and understanding, support and guidance as well as planned intervention programs in order to equip them with the necessary skills to ensure the grounded change in curriculum can be successfully initiated and the NPCS is a reality.